THE EFFECTS OF CADMIUM ON THE TRANSPORT PROCESSES IN PROXIMAL TUBULAR CELLS OF KIDNEYS - Pejovic, Teodora; Kovacevic, Sanjin; Nesovic Ostojic, Jelena (HEALTH CARE, 2022)
Cadmium (Cd) is an extremely toxic metal that is widespread in nature. Due to its favorable properties, it was widely used in the industry for the production of alkaline batteries, accumulators, pigments, and colored alloys. However, it has been shown that exposure to low concentrations of cadmium leads to damage to many organs and organ systems, and the use of this metal in industry is reduced, and it is replaced by other, less harmful materials. Today, fossil fuel combustion and cigarette consumption are important sources of cadmium exposure. Numerous studies have examined the toxic effects of cadmium and they highlight the kidneys, liver, gonads as the organs that suffer the most damage. The kidneys, as the main place of cadmium storage in the body, are mostly exposed to its toxic effects. In the proximal tubular cells of the kidney, exposure to cadmium disrupts transport processes. Although ionized cadmium (Cd2+) is thought to be largely responsible for the damage that occurs, the role of the cadmium and metallothionein complex (Cd-MT) cannot be ignored. Peritubular exposure to ionized cadmium indirectly leads to a decrease in the activity of the Na+/L-alanine cotransporter and a decrease in the rate of slow repolarization of the luminal membrane, while the Cd-MT complex leads to both direct and indirect inhibition of this transporter. Also, the Cd-MT complex inhibits Na+/Glucosa cotransporter activity. Exposure to cadmium also leads to a decrease in the endocytic uptake of low molecular weight proteins, which is accompanied by microalbuminuria.
Keywords: cadmium, proximal tubules, transport, nephrotoxicity